Mengkaji Revolusi Mental dalam Perspektif Pendidikan Kristen [Assessing the Mental Revolution from a Christian Education Perpective] - Mulyo Kadarmanto (Polyglot, 2016)
Mental Revolution is a priority program of the Indonesian government that aims to produce individuals with good character, an independent mindset, and a national identity that makes them ready to compete in the global era.  It also aims to help them see education as the main path to implementing this mental revolution, particularly in character development. Through a review of the literature, the writer will examine the Mental Revolution from the perspective of Christian education:  its background, its processes, and its objectives.  By comparing and analyzing the Mental Revolution, this study will show the uniqueness of Christian education in realizing transformative education that produces learners as restorative persons, servants, and globalizer in all aspects of life.BAHASA INDONESIA ABSTRAK: Revolusi mental sebagai program prioritas pemerintah Indonesia memiliki tujuan untuk menghasilkan individu dan bangsa yang berkarakter, mandiri dan beridentitas dalam menjadikan bangsa yang siap berkompetisi di era global; dan melihat pendidikan sebagai jalur utama melaksanakan revolusi mental, terutama dalam mengembangkan karakter. Melalui tinjauan literatur, penulisan akan mengkaji revolusi mental dari perspektif pendidikan Kristen; latar belakang, proses, dan tujuan dari revolusi mental. Dengan membandingkan dan menganalisis revolusi mental, diharapkan kajian ini dapat menampilkan keunikan pendidikan Kristen dalam mewujudkan pendidikan yang transformatif untuk menjadikan nara didik sebagai restorater, penatalayan dan globalizer dalam seluruh aspek kehidupan di era global.